Liver tests, cardiovascular outcomes and effects of empagliflozin in patients with heart failure and preserved ejection fraction: the EMPEROR-Preserved trial: research article - Böhm, Michael; Butler, Javed; Krawczyk, Marcin; Mahfoud, Felix; Haring, Bernhard; Filippatos, Gerasimos; Ferreira, João Pedro; Pocock, Stuart J.; Brückmann, Martina; Ofstad, Anne Pernille; Schüler, Elke; Wanner, Christoph; et al. (European journal of heart failure, 2023)
Aim The prognostic implication of elevated liver tests in heart failure with preserved ejection fraction (HFpEF) is uncertain. This analysis investigates the association of liver markers with hospitalization for heart failure (HHF) and cardiovascular death (CVD), and the treatment effect of empagliflozin across the range of liver marker levels. Methods and results The double-blind, placebo-controlled EMPEROR-Preserved (EMPagliflozin outcomE tRial in Patients With chrOnic heaRt Failure with Preserved Ejection Fraction) enrolled 5988 patients with HFpEF (ejection fraction >40%). Patients in New York Heart Association class II-IV and elevated N-terminal pro-B-type natriuretic peptide were randomized to receive empagliflozin 10 mg daily or placebo in addition to usual therapy. Patients with significant liver disease were excluded. The primary endpoint was time to first adjudicated HHF or CVD. We explored the association of liver function abnormalities with heart failure outcomes in patients on placebo, the effects of empagliflozin on liver tests and the treatment effects of empagliflozin on heart failure outcomes across categories of liver laboratory values. High alkaline phosphatase (p trend < 0.0001), low albumin (p trend < 0.0001) and high bilirubin (p = 0.02) were associated with poorer outcomes for HHF or CVD, while high aspartate aminotransferase was not, and high alanine aminotransferase was associated with better outcomes. Empagliflozin had no significant effects on liver tests compared to placebo except for albumin which was significantly increased. The treatment effect of empagliflozin on outcomes was not modified by liver tests. Conclusion Abnormalities of liver function tests are associated differently with heart failure outcomes. Salutary effects of empagliflozin on liver tests were not observed although albumin increased. The treatment benefits of empagliflozin were not affected by baseline values of liver parameters.
Online veröffentlicht: 6. Juni 2023
Gesehen am 28.03.2024